Multimodality and Educational Discourse - Santamaría, Dulce María (2015)
This article refers to multimodality and the educational environment. It analyzes this discipline and how the discourse it uses modifies the educational environment until it generates a new virtual culture, thus transforming students and teachers into active participants of this new culture and its resources. The mediate analysis of discourse suggested by Scollon (2008) was used as analysis methodology. There, he indicated the way related to discursive practices applied in the virtual multimodal mappings, and how they affected the educational practice. Finally, after analyzing those social practices, we reached some conclusions of interest: multimodality transforms the current educational environment into an interactive one, where teachers and students must be trained regarding virtuality and where they must be aware of the new cyberculture being generated. Teachers and students are now interrelated since